Falklands: facts and fiction - Morrone, Juan José (2005)
A reply to McDowall, R.M. (2005) Falkland Islands biogeography: converging trajectories in the South Atlantic Ocean. Journal of Biogeography, 32, 49–62. A recent contribution (McDowall, 2005) analysed the biogeography of the Falkland Islands, an archipelago situated in the south‐western Atlantic, known in Spanish as Islas Malvinas. After reviewing the literature, McDowall (2005) concluded that the biotic and geological connections of the Falklands conflict with each other because the biota shows apparent relationships with Patagonia, whereas the geology suggests a historical relationship with South Africa. He considered that these results indicate that Croizat's dictum that ‘earth and life evolve together’‘does not have general application in the way that some believe it has’ (McDowall, 2005, p. 59), thus ruling out vicariance as an appropriate explanation for the evolution of the Falklands’ biota.